(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
An experiment was conducted to study the effects of salinity, and fertilisation on wetland rice production. It was a factorial design with four levels of salinity and three levels of fertilisation. Rice plants were grown in wetland system under greenhouse conditions. Fertiliser treatments were imposed at planting. Following germination salinity treatments were imposed. Plants and soils were sampled 10 weeks after planting. Plant dry weight increased with increasing inorganic fertiliser application and decreased with increasing salinity. Total shoot N increased with increasing inorganic fertiliser application but was not affected by salinity, however total root N increased with increasing inorganic fertiliser addition and decreased with increasing level of salinity (0, 50 and 100 ppm). Plant dry weight decreased with increasing salinity. Plant dry weight and N contents in shoot and root were significantly higher in all inorganic fertiliser treatments compared to the control treatments. % Ndff was in the range of 30-50 % and increased with increasing fertiliser application and salinity. Fertiliser use efficiency was in the range of 67.87-72.8 % in the inorganic fertiliser treatment. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.21998 Bangladesh J. Sci. Ind. Res. 49(2), 69-78, 2014